Hydroxocobalamin for the treatment of vasoplegia after lung transplantation: A case series - Anh Nguyen, MD, PhD; Rima Bouajram, PharmD; Marek Brzezinski, MD; Sahand Hassanipour; David Gordon; Binh Trinh, MD; Tobias Deuse, MD; Aida Venado, MD; Steve Hays, MD; Jonathan Singer, MD; Jasleen Kukreja, MD, MPH (JHLT Open)
Background: The use of hydroxocobalamin following lung transplantation has not been previously reported. We present a series of 3 cases where hydroxocobalamin was used to treat postoperative vasoplegia. Methods: We conducted a single-center, retrospective review of lung transplantation recipients from January 2016 to December 2020. We used cumulative vasopressor index to standardize vasopressor dose administered and mean arterial pressure at 2- and 24-hour time-points following hydroxocobalamin administration to assess treatment effectiveness. Results: We identified 3 male patients aged 49 to 62, with lung allocation scores between 89.9 and 90.6, requiring extracorporeal membrane oxygenation support (pre- and post-transplant for 5, 5, 9 and 8, 2, 2 days, respectively). Each patient received hydroxocobalamin 5,000 mg infused over 15 minutes, with patient #3 receiving an additional 6 doses over the subsequent 4 days. At the 2-hour time-point, mean arterial pressure increased in all patients (+11%, +17%, and +13%, respectively), although cumulative vasopressor indexes were inconsistent. At 24 hours, patients #1 and #2 demonstrated a marked increase in mean arterial pressure (36% and 23%, respectively) and a decrease in cumulative vasopressor index, while patient #3 displayed stable with slight reduction in cumulative vasopressor index and mean arterial pressure values. No allergic reactions were observed. Patient #3 developed methemoglobinemia and a medication-related false increase in triglycerides. All 3 patients were discharged home. Conclusions: Hydroxocobalamin may be a valuable adjunct in managing refractory vasoplegia following lung transplantation.